The incursion of Ecuadorian police forces into the Mexican embassy in Quito, in light of International Law - Novak, Fabián (2024)
The purpose of the article is to resolve four questions raised in the case of the raid by Ecuadorian police forces on the Mexican embassy in Quito, which occurred on April 5, 2024, with the purpose of abducting the Ecuadorian politician Jorge Glas, granted asylum in said mission diplomat. The first refers to the legality or not of the incursion of the Ecuadorian police authorities into the Mexican embassy. The second rather aims to establish whether Ecuador’s argument regarding a possible poor granting of asylum to Jorge Glas legitimized its incursion into the Mexican diplomatic premises. The third question is whether Ecuador’s removal of the asylum seeker from the diplomatic premises constituted a violation of international law in itself. And finally, the fourth is whether Mexico violated international law by granting asylum to Jorge Glas.